Evolutionary model for glacial lake-outburst fans at the ice-sheet front : Development of meltwater outlets and origins of bedforms - Weckwerth, Piotr; Kalińska, Edyta; Wysota, Wojciech; Krawiec, Arkadiusz; Alexanderson, Helena; Chabowski, Marek (Geomorphology, 2024)
Large-scale landforms originated from jökulhlaups or glacial lake-outburst floods (GLOFs), and their small-scale components help in recognising the sedimentary environment of the flood. The GLOF fans that developed along the Pleistocene ice-sheet margin have not been investigated in detail, and north-eastern Poland, with its Megaflood Landform System and Bachanowo and Szeszupka fans, seems ideal for landform and sedimentary studies. This paper provides (1) an important opportunity to recognise the origins of glacier lake-outburst flood outlets and their evolution during two GLOFs and (2) a model of the origin of ice-marginal fans considering changes in sedimentary environment reflecting flood stages. During the first GLOF (GLOF1), the rising stage of meltwater burst triggered the formation of a supraglacial outlet and the development of the Szeszupka outburst fan. During the pulsed peak discharge, subglacial multi-channelised meltwater outburst caused the formation of the Bachanowo Gate, which was finally transformed at the flood waning stage. Such processes were associated with the widening of the floodwater subglacial routeway, when floodwater outlets rapidly spread across the glacier snout. In contrast, GLOF2 was responsible only for the Szeszupka fan erosion and development of outburst terraces. The small-scale bedforms continuum, recognised on the outburst fan surface, is associated with the development of streamlined erosional residuals, scours and their trains during the rising stage and peak discharge, while the waning stage and very end of flood conditions were favourable to the formation of pendant bars, distributive channels with erosional bars and chute bars, regardless of the feeding systems of the outburst fans. The fan deposits were OSL-dated and revealed either, likely, overly old ages or an age of 13.2 ± 0.9 ka. The latter age would imply the ‘normal’ meltwater outflow having a correlation with the events in the region. Nevertheless, this age might be considered a minimum age of the flood.